AFFECTIVE, COGNITIVE, AND BEHAVIORAL MANIFESTATIONS OF BURNOUT IN PRIMARY CARE PHYSICIANS - Yadgarova N.F., Kevorkova M.A.,; Khayredinova I.I., (Central Asian Journal of Medicine, 2025)
The article discusses another contributing factor to emotional burnout syndrome-cognitive, behavioral, and emotional states. It also lists several factors influencing professional burnout observed in 120 family doctors, indicating their severity levels and the potential symptoms they may cause. The study outlines the participants' age, gender, and work experience, as well as the stages of stress, depersonalization, and burnout.